Developing Temperature-Resilient Plants: Responses and Mitigation Strategies - Prakash, Channapatna S.; Raza, Ali; Zou, Xiling; Wang, Daojie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Climate-change-induced extreme temperatures significantly impact crop production worldwide. Therefore, this Special Issue highlights several genetics, genomics, agronomic and physiological interventions in developing temperature-resilient plants.